1 Petrus dan Etika: Suatu Perspektif Dalam Memahami Gagasan Etis Surat 1 Petrus - Agus Prasetyo (Predica Verbum: Jurnal Teologi dan Misi, 2022)
1 Peter is unique in its content and argumentation strategy among the other apostolic letters. The uniqueness of his writing not only makes this letter an interesting resource for investigating theological themes but also interesting to understand the ideas that contain an ethical message. Although the ἔθος is not present explicitly in this letter, the ethical ideas in 1 Peter are presented with the idea of ἀναστροφή (1Pet.1:15, 18, 2:12, 3:1,2,16), which refers to way of life, behavior and habits, and τέλος (1Pet. 1:9, 3:8, 4:7, 4:17) which refers to the purpose of an action or movement, the end of a process, and the end point of the duration of time. This article attempts to explain some of the approaches that have been taken to understand the ethical ideas in 1 Peter, and offers a different approach, that the ethics of 1 Peter can be seen from an identity perspective; namely understanding the sociological, theological, and missiological aspects contained in the terms used by the writer of the letter to identify the reader of 1 Peter. With this perspective, the ethics of 1 Peter is not only understood as the science of good and bad behavior, but as a source that provides of shape and direction to the life of the believer as the Christians identity values.